MITOS KEHAMILAN: IKAN, CUMI-CUMI DAN UDANG PENYEBAB MASALAH KESEHATAN PADA JANIN DI PUSKESMAS TEGAL BARAT KOTA TEGAL - Riska Arsita Harnawati; Yan El Rizal Unzilatirrizqi Dewantoro (Jurnal Ilmiah Kebidanan Imelda, 2025)
Myths are traditions that are widely spread throughout society. One myth that often arises and spreads quickly is related to health issues. West Tegal is a region in Indonesia located on the north coast of Java, with easy access to sources of protein or seafood. However, there is a myth that makes pregnant women reluctant to consume seafood because it is considered dangerous for the fetus. This study aims to examine myths related to pregnancy from the cultural perspective of the West Tegal community, Tegal City, using a qualitative approach with pregnant women as respondents. Respondents were selected using purposive sampling and accidental sampling techniques, namely pregnant women who underwent antenatal care (ANC) at the West Tegal Community Health Center and were willing to be informants. Data collection was carried out through in-depth interviews to explore the experiences, views, and beliefs of four pregnant women regarding food myths during pregnancy. The results showed that pregnant women in the working area of the Tegal Barat Community Health Center, Tegal City, still practiced pregnancy care that was not in accordance with health theory. During pregnancy, they believed in myths about food restrictions, such as not eating fish because it causes itching/allergies in the fetus, squid because it causes the fetus's skin to turn black, and shrimp because it causes the fetus's skin to become scaly.